2016
DOI: 10.1088/1674-4926/37/12/123001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thickness on strain state and surface morphology of AlN grown by HVPE

Abstract: AlN thick films were grown on c-plane sapphire substrates by hydride vapor phase epitaxy at high temperature. The evolution of the strain state and crystal quality of AlN with increase of thickness were investigated by transmission electron microscopy, field-emission scanning electron microscopy, Raman spectra and atomic force microscopy (AFM). As the thickness increased, the stress in the epilayers decreased gradually, which was attributed to the reaction of dislocations at the first several microns in thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 15 publications
0
45
0
Order By: Relevance
“…Miyake et al demonstrated that the AlN crystal quality can be improved significantly by high-temperature annealing [ 3 ]. By increasing the growth temperature, Sun et al obtained high-quality AlN thick films on sapphire [ 2 ]. Recently, Jiang et al studied the defect evolution in AlN homoepitaxial growth [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Miyake et al demonstrated that the AlN crystal quality can be improved significantly by high-temperature annealing [ 3 ]. By increasing the growth temperature, Sun et al obtained high-quality AlN thick films on sapphire [ 2 ]. Recently, Jiang et al studied the defect evolution in AlN homoepitaxial growth [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data allow the determination of mean values of residual stress. For all reactor designs and all optimized conditions by the authors [18][19][20][21][22][23][24][25][26][27][28], FWHM values were in the range of 100 to 600 arcsec and 500 to 800 arcsec for on-axis and off-axis peak, respectively. It is clear that the optimal temperature range is 1200-1400 • C to increase the Al mobility on the surface while avoiding sapphire degradation and/or etching [38].…”
Section: Introductionmentioning
confidence: 96%
“…In most recent papers [17][18][19][20][21][22][23][24][25][26][27][28] dealing with HVPE growth of AlN at high temperature from chlorinated precursors, intense efforts have been made to reduce defect densities caused by stress [29][30][31] before optimizing optical properties [18]. In situ etching to control void formation and stress release [17], multi-step methods to control island coalescence [32][33][34] or N/Al ratio [33,35], pulse injection of precursors [36], substrate position in turbulent flow [37] have been proposed to reduce strain, high dislocation densities and the appearance of cracks.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the weak surface migration of Al adatoms on the growth front limited the improvement of crystal quality. Therefore, many growth techniques have been developed for high quality AlN growth [11][12][13][14][15]. It has been demonstrated that high temperature annealing could significantly improve the AlN crystal quality [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that high temperature annealing could significantly improve the AlN crystal quality [11]. By increasing the growth temperature, high-quality AlN thick films were obtained by homemade high temperature hydride vapor phase epitaxy [12]. Sun et al revealed the mechanism of different initial conditions on the quality of AlN and got high quality AlN on sapphire substrate by a "two-step" method [13].…”
Section: Introductionmentioning
confidence: 99%